Free Prior and Informed Consent to mine development in the Yukon: Norms, Expectations, and the Role of Novel Governance Mechanisms - Martin, Emily (University of Guelph, 2018)
The adoption of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) has catalyzed Indigenous rights conversations in Canada around Free, Prior and Informed Consent (FPIC). The Yukon territory, where a majority of First Nations have self-government and settled land claims, provides a unique case for assessing how FPIC is being defined and exercised in light of possible mine developments. Findings from semi-structured interviews and document review revealed limited explicit engagement with FPIC by key Yukon governance institutions. This thesis serves to identify and make sense of this situation in an exploratory way, offering three factors: time, treaty implementation priorities, and awaited federal action, to explain the apparent lack of institutional engagement with FPIC. Despite instances of consent-like rights held by First Nations in the Yukon, there remains a lack of clear articulation from a majority of these First Nations about expectations for the meaningful expression of consent. Through a case study with the Little Salmon Carmacks First Nation (LSCFN), this research revealed that although LSCFN’s expectations of FPIC are not fully formed as of yet, they include: early and ongoing engagement, full and accessible information, internal engagement and governance processes, the mitigation of resource barriers, enforceable commitments, contextually relevant and mutually agreed upon processes, appropriate representation, agreed upon definitions, and the mitigation of power imbalances. Given the reticence of the State to acknowledge and implement FPIC this thesis also evaluates the treatment of FPIC by the Initiative for Responsible Mining Assurance (IRMA) standard, and largely confirms the comprehensiveness of that novel governance process relative to LSCFN’s emerging expectations around FPIC. Social Sciences and Humanities Research Council of Canada University of Guelph Northern Scientific Training Program